Advanced Practice Nursing Competency Assessment Instrument (APNCAI): clinimetric validation. Issue 2 (23rd February 2017) - Sastre-Fullana, Pedro; Morales-Asencio, Jose Miguel; Sesé-Abad, Albert; Bennasar-Veny, Miquel; Fernández-Domínguez, Juan Carlos; De Pedro-Gómez, Joan
Abstract : Objective: To describe the development and clinimetric validation of the Advanced Practice Nursing Competency Assessment Instrument (APNCAI) through several evidence sources about reliability and validity in the Spanish context. Design and setting: APNCAI development was based on a multisequential and systematic process: literature review, instrument content consensus through qualitative Delphi method approach (a panel of 51 Advanced Practice in Nursing –APN– experts was selected) and the clinimetric validation process based on a sample of 600 nurses from the Balearic Islands public healthcare setting. Methods: An initial step for tool's content development process based on Delphi method approach of expert consensus was implemented. A subsequent phase of tool validation started from the analysis of APN core competencies latent measurement model, including exploratory and confirmatory techniques. Reliability evidence for each latent factor was also obtained. Items' scores were submitted to descriptive analysis, plus univariate and multivariate normality tests. Results: An eight-factor competency assessment latent model obtained adequate fit, and it was composed by 'Research and Evidence-Based Practice', 'Clinical and Professional Leadership', 'Interprofessional Relationship and Mentoring', 'Professional Autonomy', 'Quality Management', 'Care Management', 'Professional Teaching and Education' and 'Health Promotion'. Conclusions: Adequate empirical evidence of reliability and validity for APNCAI makes it useful for application in healthcare policy programmes for APN competency assessment in Spain.